Legal Consequences for Companies and Workers Due to Not Registering for BPJS Employment - Sanco Simanullang; Habieb Pahlevi; Elisabet Rawati Girsang; Yasir Riady (PT FORMOSA CENDEKIA GLOBAL, 2025)
BPJS Ketenagakerjaan is a mandatory social security program for companies and workers in Indonesia. This obligation is regulated by law to protect workers from risks such as workplace accidents, death, and retirement. However, many companies still fail to fulfill this obligation. Such non-compliance can lead to legal consequences, including administrative and criminal sanctions. On the other hand, workers become vulnerable to various risks without social security protection. This article examines the legal aspects governing company obligations, implications for workers, and potential sanctions faced. This study aims to provide a deeper understanding of the importance of compliance with BPJS Ketenagakerjaan registration. Raising awareness and enforcing the law are necessary to ensure fair protection for all stakeholders.